Упростите выражение 15-9^2^3*15+9^2^3

упростите выражение (15-9^2)^3*(15+9^2)^3

  • Выражение: (15-9^2)^3*(15+9^2)^3
    Ответ: -287496*884736
    по действиям:
    1. 9^2=81
    2. 15-81=-66
    3. (-66)^3=(-1)*287496
     3.1. (-1)^3=(-1)
      3.2. 66^3=287496
    4. (-1)*287496=-287496
    5. 9^2=81
     6. 15+81=96
     7. 96^3=884736
       8. (-287496)*884736=-287496*884736
    по шагам:
    1. (15-81)^3*(15+9^2)^3
      1.1. 9^2=81
          2. (-66)^3*(15+9^2)^3
      2.1. 15-81=-66
          -3. (-1)*287496*(15+9^2)^3
      3.1. (-66)^3=(-1)*287496
          (-66)^3=(-1)^3*66^3
        3.1.1. (-1)^3=(-1)
          3.1.2. 66^3=287496
    4. (-287496)*(15+9^2)^3
      4.1. (-1)*287496=-287496
    5. (-287496)*(15+81)^3
      5.1. 9^2=81
         6. (-287496)*96^3
      6.1. 15+81=96
        7. (-287496)*884736
      7.1. 96^3=884736
          8. -287496*884736
      8.1. (-287496)*884736=-287496*884736